Ovarian Innervation Coupling With Vascularity: The Role of Electro-Acupuncture in Follicular Maturation in a Rat Model of Polycystic Ovary Syndrome - Tong, Xiaoyu; Liu, Yanjun; Xu, Xiaoqing; Shi, Jiemei; Hu, Wei; Ma, Tong; Cui, Peng; Lu, Wenhan; Pei, Zhenle; Xu, Mingzhen; Zhang, Feifei; Li, Xin; et al. (Frontiers in Physiology, 2020)
Low-frequency electro-acupuncture (EA) has been shown to restore ovulation in patients with polycystic ovary syndrome (PCOS), and previous animal experiments showed that EA improves ovarian blood flow and angiogenesis. We performed EA for 4 weeks in dihydrotestosterone (DHT)-induced PCOS-like rats and investigated the three-dimensional (3D) ovarian innervation to determine the role of neuronal innervation in folliculogenesis and vascularity. Ovarian tissues were made transparent following the CUBIC 3D tissue-clearing protocol and were immunostained using antibodies against platelet endothelial cell adhesion molecule-1 and tyrosine hydroxylase to visualize the ovarian vasculature and innervation, respectively. This was followed by 3D imaging using light sheet microscopy and analysis using the Imaris software. In control rats, ovarian neuronal innervation increased with age, and the neuronal branching started from the ovarian hilum and reached the individual follicles at different follicle stages. At the individual follicle level, each follicle was mainly innervated by one neuronal fiber. Compared with control rats, ovaries from DHT-treated PCOS-like rats had more antral follicles and fewer pre-ovulatory follicles and corpora lutea. Furthermore, PCOS ovaries showed decreased innervation of blood vessels near the hilum and the surrounding individual antral follicles. EA in PCOS-like rats led to the increase numbers of pre-ovulatory follicles and corpora lutea, together with increased innervation of blood vessels near the hilum. To determine the role of neuronal innervation, we further performed unilateral sectioning of the superior ovarian nerve in PCOS+EA rats and found that the left sectioned ovary had fewer pre-ovulatory follicles and corpora lutea compared with those in the right non-sectioned ovary. In conclusion, ovarian neuronal innervation likely plays an important role in folliculogenesis, and EA might improve PCOS pathophysiology by regulating ovarian neuronal innervation, at least partially mediated through the superior ovarian nerve.